The disability option: Labor market dynamics with macroeconomic and health risks - Amanda Michaud; David Wiczer (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2018)
We evaluate the contribution of changing macroeconomic conditions and demographics to the increase in Social Security Disability Insurance (SSDI) over recent decades. Within our quantitative framework, multiple sectors differentially expose workers to health and economic risks, both of which affect individuals' decisions to apply for SSDI. Over the transition, falling wages at the bottom of the distribution increased awards by 27% in the 1980s and 90s and aging demographics rose in importance thereafter. The model also implies two-thirds of the decline in working-age male employment from 1985 to 2013, three-fourths of which eventually goes on SSDI.
Keywords: 330